The Influence of Facilities, Company Image and Customer Perceptions on Purchasing Decisions in Using PT Expedition Services. Eight Primary Oceans - Ihdina Gustina; Bambang Sutejo (Outline Journal of Management and Accounting, 2023)
This study aims to determine the effect of Facilities, Company Image and Customer Perception on Decision of Buyers at PT. Delapan Samudera Pratama. The population in this research is the consumer from PT. Delapan Samudera Pratama as much as 2,496 respondent. The technique of determining the number of samples used in this study is the Slovin formula and totaling 96 respondents. The results of the analysis show that the Facilities partially has no effect on Decision of Buyers at PT. Delapan Samudera Pratama. The results showed that Company Image and Customer Perception partially have a positive and significant effect on Decision of Buyers at PT. Delapan Samudera Pratama. The results showed that Facilities, Company Image and Customer Perceptions simultaneously have a positive and significant effect on Decision of Buyers at PT. Delapan Samudera Pratama. The results of this study are supported by the value of R Square which mean Facilities, Company Image and Customer Perceptions can explain decisions of buyer and the remaining is influenced by other variables outside of this study such as price, and service quality.